In Vitro plant regeneration from leaf explants of Tagetes erecta L. - Munshi, JL; Baksha, R; Rahaman, MZ; Huque, NN; Zinat, EA; Momtaz, N (Bangladesh Journal of Scientific and Industrial Research, 2021)
Regeneration of multiple shoots via callus induction and organogenesis was obtained from young leaf explants of the field grown marigold (Tagetes erecta L.). Callus induction and shoot regeneration at various frequencies were observed using different concentrations and combinations of growth regulators. Highest percentage (90%) of callus formation was observed within two weeks on MS medium supplemented with 5.0 mg/l BAP with 2.5 mg/l NAA. The maximum percentage (80%) of shoot bud formation (10±0.5/callus) was obtained from MS medium containing 1.0 mg/l BAP with 0.5 mg/l kinetin. The regenerated shoots developed highest percentages (90%) of roots on half strength MS medium supplemented with 1.0 mg/l IBA. The plantlets when transferred into potsoil 80% survived. Regenerated plants were morphologically uniform with normal leaf shape and growth pattern. Bangladesh J. Sci. Ind. Res.56(2), 69-74, 2021